If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4n + 2 = -2(n + 2) Reorder the terms: 2 + 4n = -2(n + 2) Reorder the terms: 2 + 4n = -2(2 + n) 2 + 4n = (2 * -2 + n * -2) 2 + 4n = (-4 + -2n) Solving 2 + 4n = -4 + -2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2n' to each side of the equation. 2 + 4n + 2n = -4 + -2n + 2n Combine like terms: 4n + 2n = 6n 2 + 6n = -4 + -2n + 2n Combine like terms: -2n + 2n = 0 2 + 6n = -4 + 0 2 + 6n = -4 Add '-2' to each side of the equation. 2 + -2 + 6n = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 6n = -4 + -2 6n = -4 + -2 Combine like terms: -4 + -2 = -6 6n = -6 Divide each side by '6'. n = -1 Simplifying n = -1
| 3x+2.5=17.5 | | 16x^2-9y^2=729 | | 4r=-11 | | ln(x+1)+ln(x-1)=6 | | -2(1x+8)+3=5 | | 2-4(x+2)=4 | | 4=-14a+19b | | 2(-3n+5)=-4(n+4) | | 5-(2x-6)=5x+8 | | 8f+2+9=3f-f+29 | | 12+k*8=84 | | -52=4(5+6x) | | 142=x^2+8x | | 26=2(8+x) | | 10ab-6ab= | | 7(-7+4x)=118 | | 7(6+x)=6(x-3) | | -3(2n-3)=4(5-n) | | y-3*13=13 | | 7(C+2)=3C-5+4C+9 | | 5=4k+53 | | z/4=30 | | 2(9x-8)=19x-15 | | 5x-17=3x+10 | | 2x(5-3)-3=5 | | 4(6)+3= | | 3y+12x=-11 | | 1.1x+1.2+-5.4=-10 | | 8k(4-6)-2x=16(3-k) | | 8(2x-3)-4=6x+9x-1 | | 30x-3x=X-2 | | 6x+15-7= |